Application of Health Education Prescriptions in Patients with Vulvovaginal Candidiasis - Hu Nüying; Wang Ao; Liu Jie (Ilmu Inovasi Nusantara, 2026)
Vulvovaginal candidiasis (VVC) is a common gynecological infection with a high recurrence rate, posing significant challenges for long-term disease management. Although antifungal therapy remains the mainstay of treatment, its effectiveness is often limited by inadequate patient knowledge, poor treatment adherence, and insufficient lifestyle and hygiene management. These limitations highlight the need for complementary non-pharmacological interventions, particularly structured health education strategies, to improve clinical outcomes and prevent recurrence. This study aimed to investigate the effectiveness of health education prescription interventions in improving clinical symptoms, signs, and recurrence rates among patients with VVC. A total of 200 patients diagnosed with VVC and meeting the inclusion criteria were randomly assigned to an experimental group (n = 100) and a control group (n = 100). Both groups received standard antifungal drug treatment. In addition, the experimental group received a structured health education intervention for 6 months, including education on disease knowledge, medication guidance, personal hygiene, lifestyle modification, and strategies to prevent recurrence. Clinical symptom and sign scores were assessed before intervention, during mid-treatment, and after treatment. The number of VVC recurrences during the intervention period was also recorded. Statistical analysis was performed to compare outcomes between the two groups. There were no statistically significant differences between the two groups in baseline characteristics or pre-intervention indicators (p > 0.05). Following intervention, both groups showed improvements in symptom and sign scores and reduced recurrence rates. However, the experimental group demonstrated significantly lower symptom and sign scores and a markedly lower recurrence rate than the control group (p < 0.05). Health education prescription interventions can significantly enhance the effectiveness of conventional VVC treatment by improving symptom control and reducing recurrence. This approach has significant clinical value and warrants broader implementation and further research in gynecological practice